Correlation between Derived Neutrophil to Lymphocyte Ratio and D-Dimer in COVID-19 Patients - Natra Dias Surohadi; Ria Triwardhani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Several studies suggest that the Derived Neutrophil to Lymphocyte Ratio (d-NLR) and d-dimer are markers of inflammation in various diseases and can be used to monitor prognosis and mortality. This study was conducted to find the correlation between Derived Neutrophil to Lymphocyte Ratio (d-NLR) and d-dimer in COVID-19 patients. This is expected to be markers of inflammation and a predictor for patients which has clinical deterioration so that the risk of death can be avoided. This study used a retrospective observational method with a cross sectional approach at Dr. Kariadi Semarang, using secondary data involving confirmed COVID-19 respondents during the period March - August 2020. The Spearman test was conducted to analyze data, significant if p <0.05. Thirty three respondents confirmed COVID 19 with median value of  d-NLR 6,14 (3,55-15,67) and median value of d-dimer 7110 (2460-21770) mg/L were tested for correlation by the Spearman correlation test with value of p= 0,046; and r= 0,350. In COVID-19, there is an increase in d-NLR and d-dimer levels which are known as markers of a systemic inflammatory response. The increase in levels is related to the severity of the COVID-19 disease. There was a highly significant positive correlation between d-NLR and d-dimer in COVID-19 patients